Effect Of Water Restriction On Physiological Responses Of Indigenous Hoggets In Middle Gujarat Agro Climatic Condition - Patel, N.R.; Islam, M.M.; Modi, R.J.; Wadhwani, K.N. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Eighteen farm born unshorn hoggets (25-30 kg) of Patanwadi and Marwari breeds of sheep were selected and randomly divided into three treatment groups on the basis of body weight comprising of six in each group, viz., T1: Control (ad.lib. water), T2: (WR1-20% water restriction), T3: (WR2- 40% water restriction) to study the effect of water restriction (WR, for 28 days) on physiological responses. The experimental animals under T3 showed significantly (P<0.05) higher pulse rate than T2 and T1 at 7.30 am, whereas the pulse rate recorded at 2.30 pm was significantly (P<0.05) higher under T3 than T1 and at par with T2 as a result of water restriction. The animals under T3 showed significantly (P < 0.05) higher respiratory rate than T1 and T2 at 7.30 am whereas at 2.30 pm, the respiratory rate was at par among the treatment groups. Rectal temperature (°F) recorded at 7.30 am and 2.30 pm did not differ significantly due to water restriction. The changes observed in physiological responses indicated the adaptability of the animals to increased thirst periods.